Public Administration Study: The Role and Challenges of Public Administration in the Era of Globalization - Bambang Agus Diana; Yusup Lintang Cahyo Andrian Putro (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
Public administration is a universal phenomenon, existing since the dawn of world civilization. It continues to evolve alongside changes in world civilization, facing various challenges, including the era of globalization and digitalization. Public administration, as one of the sciences that drives social change, promotes the democratization process of government that favors the powerless people (the poor or vulnerable). The writing employs a literature review approach to outline the role of public administration in addressing global challenges. The role of public administration as the key to modern society, as expressed by Charles A. Beard, who argued that no other subject is more important than administration. In the era of globalization, public administration as an artistic science generally remains important in state management, which aims to improve the standard of living in the nation. The government must address globalization's effects so that its benefits can be maximized and its drawbacks avoided. Therefore, the role of state administrators as public servants is crucial in controlling social life and ensuring the welfare of their people.